Hubungan Pengetahuan dan Sikap dengan Pemeliharaan Instalasi Pengolahan Air Limbah Komunal Berbasis Masyarakat di Kecamatan Tamalate Kota Makassar - Ariaty B, Eka; Daud, Firdaus; Bahri, Arsad (Universitas Negeri Makassar, 2020)
Abstract.Â This research aims to find out: the knowledge and the attitude of community environmental sanitation in Tamalate Subdistrict, Makassar City, and the maintenance of Community- based Communal Wastewater Treatment Plant in Tamalate Subdistrict, Makassar City, the relationship between environmental sanitation knowledge and maintenance of Community-Based Wastewater Treatment Plant in Tamalate Subdistrict, Makassar City, the relationship between knowledge of environmental sanitation and the maintenance of Community Based Wastewater Treatment Plant in Tamalate subdistrict, Makassar City. This research was a quantitative descriptive research with applying a correlational approach. The population of this research was all household users from 10 locations of communal Wastewater Treatment Plant in Tamalate District, Makassar City. The sampling technique was conducted by using purposive random sampling technique. The instruments of this research used knowledge tests, attitude questionnaires and observation sheets. The results of this research showed that the knowledge of environmental sanitation of user community and Communal IPAL administrators in Tamalate Subdistrict, Makassar City is in the high category. and the knowledge are significantly related and positive direction with maintenance of Community-Based Wastewater Treatment Plant in Tamalate Subdistrict, Makassar City, it is influenced by education level and the socio-economic conditions are still low but if the knowledge and attitude of the community is good, then the maintenance of IPAL will also be good.Â Keywords:Â knowledge, environmental sanitation, maintenance of IPAL